MODERN CLINICOSOCIAL CHARACTERISTICS OF FIRST-REVEALED TUBERCULOSIS OF RESPIRATORY APPARATUS IN WOMEN OF TUVA REPUBLIC - N. M. Koretskaya (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
We realized, the analysis of 134 cases of first-revealed tuberculosis of respiratory apparatus in women of Tuva Republic. We detected, prevalence of disseminate affections, high, frequency of dissociation, and bacterioexcre-tion (in 86,9 % of cases — excretion of drug-resistant bacteria, half of them, has plural drug resistance and. one third, has high, vitality, that proves high, epidemiologic risk of ill people). We marked, out factors of risk of tuberculosis morbidity in women and. determined, their significance in development of specific process. It was shown that disease in every fourth, woman is connected, with, pregnancy and. birth. We concluded, necessity of obligatory checking fluoroscopy for all women in puerperal period, during their stay in maternity hospital.